Chronica Epigraphica Celtiberica XI (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2022)
Celtiberian inscribed pieces published between 2018 and 2021 are presented. These are: a spindle whorl from Horcajada de La Torre (Cuenca), a tessera from Uxama Argaela (El Burgo de Osma, Soria), two tesserae from Virovesca (Briviesca, Burgos), part of a bronze sheet found in El Castillo de Rabanera (Ventosa, San Pedro Manrique, Soria) and the fragment of the bronze from Novallas (Zaragoza). The reading of the spindle whorl from Arcobriga, [K.7.1] = [Z.04.01], is also revised.
Keywords: Celtiberian epigraphy; spindle whorl; tessera; bronze sheet; bronze plate